An Observational Single-Center Study: Comparison of the 29-mm Sapien 3 With the 34-mm Evolut-R in Patients With a Large Aortic Annulus - Ronan Canitrot; Vincent Bataille; Anthony Matta; Bertrand Marcheix; Etienne Grunenwald; Didier Carrie; Jérôme Roncalli; Frédéric Bouisset; Clément Servoz; Francisco Campelo-Parada; Thibault Lhermusier (Journal of Interventional Cardiology, 2025)
Conclusion: In patients with a LAA who require a TAVI, the 34-mm ER and 29-mm S3 prostheses demonstrate significant differences in hemodynamics with no impact on cardiovascular mortality.